Effects of the timing of the initiation of dietary intake on pediatric type 1 diabetes for diabetic ketoacidosis - Xuewen Yuan; Jieguo Wang; Xiaofeng Chen; Wu Yan; Qing Niu; Ning Tang; Ming Zhi Zhang; Wei Gu; Xu Wang (BMC, 2022)
Abstract Background Precision treatment of pediatric diabetic ketoacidosis (DKA) has been the focus of research for decades. Whether the timing of the initiation of dietary intake contributes to DKA correction is ignored. Methods We conducted a retrospective study to investigate the effects of the timing of the initiation of dietary intake on DKA correction in Children's Hospital of Nanjing Medical University, a tertiary children's hospital, from June 2017 to December 2020. Individual basic characteristic and clinical information of all DKA cases (n = 183) were collected. Multiple linear regression, logistic regression model and random forest (RF) model were used to assess the effect of the timing of the initiation of dietary intake on DKA correction. Results The mean age of the children diagnosed with DKA was 6.95 (SD 3.82) years. The median DKA correction time and the timing of the initiation of dietary intake was 41.72 h and 3.13 h, respectively. There were 62.3% (n = 114) patients corrected DKA at the end of the 48-h rehydration therapy. For each hour delay in starting dietary intake, child's DKA correction was prolonged by 0.5 (95% CI 1.05, 1.11, P < 0.001) hours and the adjusted odds of DKA over 48 h was increased by 8% (OR = 1.08, 95% CI: 1.05, 1.11, P < 0.001) after adjustment for potential confounders. The RF model based on the timing of the initiation of dietary intake and child's weight and systolic pressure achieved the highest AUC of 0.789. Conclusion Pediatricians should pay attention to the effect of the timing of the initiation of dietary intake, a controllable factor, on DKA correction.